2016
DOI: 10.2166/washdev.2016.027
|View full text |Cite
|
Sign up to set email alerts
|

Field trial of an automated batch chlorinator system at shared water points in an urban community of Dhaka, Bangladesh

Abstract: Point-of-use water treatment with chlorine is underutilized in low-income households. The Zimba, an automated batch chlorinator, requires no electricity or moving parts, and can be installed at shared water points with intermittent flow. We conducted a small-scale trial to assess the acceptability and quality of Zimba-treated municipal water. Fieldworkers collected stored drinking water over a 10-week period from control (n = 24 households) and treatment (n = 30 households) compounds to assess levels of free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 19 publications
2
61
0
Order By: Relevance
“…The overall municipal water quality results reported here are consistent with previous studies in Dhaka that reported high levels of fecal contamination in municipal drinking water mostly in low-income communities [17,43]. A nationally-representative water quality assessment estimated that 41% of all improved water sources sampled across Bangladesh were contaminated with E. coli [44,45].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The overall municipal water quality results reported here are consistent with previous studies in Dhaka that reported high levels of fecal contamination in municipal drinking water mostly in low-income communities [17,43]. A nationally-representative water quality assessment estimated that 41% of all improved water sources sampled across Bangladesh were contaminated with E. coli [44,45].…”
Section: Discussionsupporting
confidence: 89%
“…The high concentration of E. coli in DSCC municipal water supply may be due to the long water residence time in a water distribution system with compromised physical and hydraulic integrity that allows intrusion of contamination. Additionally, recent research on water quality in low-income urban communities in Dhaka reported that most of the municipal water sources do not have chlorine injectors and/or that the water was inappropriately treated before distribution [17,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicated that passive chlorination effectively disinfected water supplies in low-income densely populated communities, required minimal behaviour change for users, and suggested high potential for these types of technologies to increase sustained and consistent access to clean water. 12,13 The primary aim of this study was to evaluate the effect of installing novel passive chlorination devices at shared water points on child diarrhoea prevalence in low-income, densely populated communities in urban Bangladesh.…”
Section: Introductionmentioning
confidence: 99%